(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the theoretical and practical aspects of the concept of perlocutionary effect, which determines the success or failure of a perlocutionary act. It describes the variety of such effects, including expected results, partially expected results, unexpected results (i.e., negation or reverse effect), hidden effects, and mental or physical impacts. Additionally, the article discusses factors that contribute to perlocutionary outcomes.